COVID-19 in Rural India, Algeria, and Morocco: A Feminist Analysis of Small-Scale Farmers' and Agricultural Laborers' Experiences and Inventive Practices - Leonardelli, Irene; Bossenbroek, Lisa; Ftouhi, Hind; Kadiri, Zakaria; Bhat, Sneha; Kulkarni, Seema; Hamamouche, Meriem Farah; Saidani, Mohamed Amine; Zwarteveen, Margreet; Kemerink-Seyoum, Jeltsje Sanne (Frontiers in Human Dynamics, 2021)
In this paper we present a modest and situated analysis of the implications of the COVID-19 pandemic on the life of small-scale farmers and agricultural laborers in India, Algeria and Morocco, as well as their ways to reinvent their everyday life in these troubled times. We draw on data collected through phone interviews since April 2020. Inspired by feminist scholars, we analyze our findings thinking with - and entangling - the concepts of intersectionality, resilience and care. We firstly document the material impacts of the lockdown measures, focusing particularly on the experiences of single women farmers and laborers, whose livelihood and well-being are notably compromised. Secondly, we focus on how different agricultural actors have come up with inventive ways to respond to the unexpected and troubled situation which they are facing. In doing so, we highlight the importance of considering different entangled socionatural challenges, uncertainties and marginalizations that different agricultural actors face, as well as the transformative potential of their inventive practices, which are often informed by notions of care.